Filter width and uncertainty estimation in continuum modeling of particle phases. (September 2015) - Simeonov, Julian A.; Bateman, Samuel; Calantoni, Joseph
Highlights: Analyzed continuum fields produced by volume averaging uniform spheres distributions. Obtained power laws relating the filter size and the noise of the concentration field. Explained the empirical power law using a theoretical estimate of the noise.